Economic aspects of defining breeding objectives in selection programmes - Charfeddine N. (Analysis and definition of the objectives in genetic improvement programmes in sheep and goats. An economic approach to increase their profitability, 2000)
The breeding objective in any livestock species is to increase the profit by improving production efficiency. Breeding objective is described by a profit function that takes genetic values as input and produces profit as outcome. This profit may be a bioeconomic model of the farm. The traits in the profit function should be related as directly as possible to all sources of income and costs. The profit function can include variables controlled by management decisions if these interact with genetic merit. Cumulative discounted expressions should be multiplied by the economic value to give the discounted economic values. Development and implementation of selection criteria are also presented.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/11/18-20, Zaragoza (Spain)